Determinan Perilaku Penggunaan Mobile Payment: Pendekatan Technology Acceptance Model dan Theory Reasoned Action - Boki, Emi; Simanjuntak, Pranatalindo (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2025)
The Covid 19 pandemic has caused various changes, one of which is the payment process which has had a significant impact. The payment system has changed from using cash or through direct transactions to an online system without direct face-to-face contact using mobile devices or better known as mobile payment. This study uses the Technology Acceptance Model and Theory Reasoned Action approaches to test the relationship between perceived ease of use, perceived usefulness, perceived risk, and subjective norms on mobile payment usage behavior with behavioral intention as a mediating variable. This study was conducted at Hasanuddin University with 273 respondents from the postgraduate students of the Faculty of Economics and Business who were still active and using mobile payments. Data were analyzed using Analysis of Moment Structure (AMOS). The results showed that perceived ease of use, and behavioral intention had a significant effect on mobile payment usage behavior, and perceived usefulness, perceived risk, and subjective norms did not have a significant effect on mobile payment usage behavior. Other findings showed that behavioral intention mediated the influence of perceived ease of use, perceived usefulness, perceived risk and subjective norms on mobile payment usage behavior. This shows that the behavior of using mobile payments is quite easy for some students so that they feel confident that using mobile payments is easier and more effective than the direct payment process, while their intentions and behavior in using mobile payments are maximized.